2002
DOI: 10.1037/0021-9010.87.3.565
|View full text |Cite
|
Sign up to set email alerts
|

Perceived supervisor support: Contributions to perceived organizational support and employee retention.

Abstract: Three studies investigated the relationships among employees' perception of supervisor support (PSS), perceived organizational support (POS), and employee turnover. Study 1 found, with 314 employees drawn from a variety of organizations, that PSS was positively related to temporal change in POS, suggesting that PSS leads to POS. Study 2 established, with 300 retail sales employees, that the PSS-POS relationship increased with perceived supervisor status in the organization. Study 3 found, with 493 retail sales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

96
1,770
4
78

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,982 publications
(2,063 citation statements)
references
References 28 publications
96
1,770
4
78
Order By: Relevance
“…Previous research also provides evidence that POS is associated with trust (for example, Tan & Tan 2000), affective commitment (Casper, Martin, Buffardi, & Erdwins, 2002;Shore & Wayne, 1993), turnover intentions (Eisenberger, Stringlhamber, Vandenberghe, Sucharski, & Rhoades, 2002;Wayne et al, 1997), service delivery standards (Fuller, Burnett, Hester, & Relyea, 2003), innovation (Eisenberger et al, 1990), and job factors such as involvement, stress, and withdrawal behavior . In addition, Watkins (1995) found a strong correlation between the effectiveness of conversations with superiors and POS.…”
Section: Loyaltymentioning
confidence: 99%
“…Previous research also provides evidence that POS is associated with trust (for example, Tan & Tan 2000), affective commitment (Casper, Martin, Buffardi, & Erdwins, 2002;Shore & Wayne, 1993), turnover intentions (Eisenberger, Stringlhamber, Vandenberghe, Sucharski, & Rhoades, 2002;Wayne et al, 1997), service delivery standards (Fuller, Burnett, Hester, & Relyea, 2003), innovation (Eisenberger et al, 1990), and job factors such as involvement, stress, and withdrawal behavior . In addition, Watkins (1995) found a strong correlation between the effectiveness of conversations with superiors and POS.…”
Section: Loyaltymentioning
confidence: 99%
“…The most important factors that contribute to empowerment, engagement and satisfaction of employees are based on their relationship with the leader (Eisenberger et al, 2002;Rhoades et al, 2001). Bell and Kozlowski (2002) have stressed the role of leadership for the effectiveness of virtual teams.…”
Section: Leadership and Empowermentmentioning
confidence: 99%
“…Thirdly, the relationships among coworker support, supervisor support, and organizational support should be investigated. As discussed earlier, previous studies indicated that supervisor support and organizational support are highly correlated (e.g., Eisenberger et al, 2002;Woo & Chelladurai, in review). In addition, coworker support was also found to be related to supervisor support (e.g., Yoon & Thye, 2000;Woo & Chelladurai, in review).…”
Section: Sources Of Support 20mentioning
confidence: 82%
“…Eisenberger et al (2002) observed that perceived supervisor support was positively related to temporal change in perceived organizational support, suggesting that supervisor support leads to organizational support. Additionally, they noted that supervisor support-organizational support relationship rose with perceived supervisor status, suggesting that the higher the perceived standing of a supervisor within the organization, the more likely would be that an employee perceived his or her supervisor as the organization representative.…”
Section: Organizational Supportmentioning
confidence: 96%
See 1 more Smart Citation